Implications of corporate capital structure theory and financing patterns for capital market development in Trinidad and Tobago. - SEERATTAN, Dave A. (1996)
Reviews the literature on optimal corporate capital structure, theory and corporate financing patterns in various countries. Examines corporate financing patterns in Trinidad and Tobago. Discusses policy implications for capital market development in Trinidad and Tobago.